How does E-commerce live streaming affect Chinese consumers' purchase intention - Qi, Mengjia; Lunyai, Janifer Anak (Edelweiss Applied Science and Technology, 2025)
Among many marketing models, e-commerce live streaming has rapidly become a mainstream commercialized marketing approach by integrating consumer attributes of e-commerce with the rapid user acquisition capabilities of live streaming. Although e-commerce live streaming is continually promoted in practice, its effect on online consumption intentions still lacks sufficient theoretical and empirical support. Understanding how e-commerce live streaming influences online purchasing intentions can provide valuable references and suggestions for e-commerce websites and sellers to maximize the marketing potential of live streaming, thereby enhancing market competitiveness. Additionally, this understanding can expand research on the commercialized marketing mode of live streaming, offering a solid theoretical foundation. This study focuses on e-commerce live streaming as the research subject, exploring its impact on consumers' online purchase intentions. It considers the tripartite interaction system formed by consumers, sellers, and live streaming platforms. Based on socio-technical theories, the study analyzes in depth how the technical features and service quality of e-commerce live streaming influence purchase intentions. Data for this research was obtained through a questionnaire survey.